EL GENERO LYCOPODIOPSIS (LYCOPODIOPSIDACEAE, LEPIDODENDRALES), DEL CARBONICO MEDIO-PERMICO INFERIOR DE ARGENTINA (Ameghiniana, 2013)
"The present paper is a revision of the Argentine specimens of arborescent Lycopsida, here attributed to Lycopodiopsis Renault em. Krausel.Three species are described: L. derbyi Ren., L. millani n.sp, and L. pedroanus (Carr.) Zeil. Under each taxon, the synonimy, types, features, remarks, geographycal and stratigraphycal distribution and photographs are given. It is concluded that Lycopodiopsis in Argentina is found from the Middle Carboniferous (Paganzo basin) up to Lower Permian (Patagonia)."